American paraliterature and other theories to hijack communication - Stricklin, Blake (Anthem symplokē studies in theory., 2021)
American Paraliterature examines the generative encounters of post-1968 French theory with the postwar American avant-garde. The book begins with an account of the 1975 Schizo-Culture conference that was organized by Semiotext(e) editor Sylvère Lotringer at Columbia University. The conference was an attempt to directly connect the American avant-garde with French theory. At the event, John Cage shared the stage with Deleuze and Foucault introduced William S. Burroughs. This schizo-connection presents a way to read the experimental methods of the American avant-garde (Burroughs, Cage, and Kathy Acker), and how their writing creates a counterprogram to the power that Foucault and Deleuze started to articulate in the 1970s.